Heavy metals concentration in “etak” tissue at different processing stages - Dee Koh, Han; Abdullah, Faizuan; Ibrahim, Idanne Adilla; Rozaki, Nurul Inani; Md Nasir, Siti Nor Aini; Suganthi, Appalasamy; Md Nasir, Siti Nor Aini; Mohd Ghazi, Rozidaini; Abdullah, Nor Hakimin; Eh Rak, Aweng (UMK Press, 2019)
Corbicula fluminea, known as “etak” in Kelantan, Malaysia is a freshwater bivalve. This clam is widely consumed as traditional snack by the locals. However, lately there are numerous reports in local newspapers that claim “etak” to cause health effects due to eating contaminated “etak”. Hence, this study aims to determine the heavy metals concentration in fresh, smoked and exposed “etak” sold at the stall as a baseline study in order to develop a method for removing the heavy metals content in its tissues. This study involves sample collection in the stalls around Kelantan, sample preparations via acid digestion and heavy metal determination using Perkin Elmer PinAAcle 900F Atomic Absorption Spectrometer. The results showed the heavy metals (Cr, Zn, Mn and Cu) concentrations (μg/g) in all “etak” tissue were at different level for fresh (Cr: 1.02±0.35ppm, Zn: 74.57±2.76ppm, Mn: 40.22±9.96ppm and Cu: 15.27±1.41ppm), smoked (Cr: 0.42±0.02ppm, Zn: 54.62±17.83ppm, Mn: 50.13±2.31ppm and Cu: 20.94±8.81ppm) and exposed (Cr: 0.53±0.08ppm, Zn: 63.07±8.44ppm, Mn: 50.41±6.92ppm and Cu: 12.80±0.40ppm) samples. The results obtained were compared with the permissible limits set by Malaysian Food Regulations 1985 (Cu: 30.0ppm and Zn: 100.0ppm), FAO/WHO 1984 (Mn: 5.4ppm) and IAEA – 407 (Cr: 0.75ppm). For fresh “etak”, Zn and Cu concentration were below the standards, while Mn and Cr were exceeded the permissible limits. For smoked “etak” and exposed “etak” at stall, all heavy metals concentration were within the permissible limits, except Mn contents. This study successfully determine the baseline concentration of the heavy metals in “etak”.